2012
DOI: 10.1136/bjophthalmol-2011-301450
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal chemotherapy for vitreous disease in retinoblastoma revisited: from prohibition to conditional indications

Abstract: This study reports the first clinically documented case series of patients with retinoblastoma treated with IViC. Despite a possible confounding effect of concomitant chemotherapy prescription using other routes of administration in four of the successfully treated eyes (20%), IViC achieved an unprecedented success rate of tumour control in the presence of vitreous seeding. Of note, none of the treated eyes required external beam irradiation to control the vitreous seeding. Further studies are required to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
297
1
14

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(322 citation statements)
references
References 19 publications
10
297
1
14
Order By: Relevance
“…15 The last data on intraarterial chemotherapy seem to show satisfactory eye preservation for first-line as well as second-line treatments. 30,31 Short-term ocular toxicity may be seen with ischemic short-term complications being described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The last data on intraarterial chemotherapy seem to show satisfactory eye preservation for first-line as well as second-line treatments. 30,31 Short-term ocular toxicity may be seen with ischemic short-term complications being described.…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal injection of chemotherapy may be an interesting tool in the management of selected cases with active vitreous seeding. 15 All these techniques can be combined to obtain the best tumor control, especially in the more advanced D group cases, these patients needing more treatments. Since the end of the study bilateral group D patients are treated by an association of six courses of three drugs chemotherapy regimen and local adjuvant therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new eye-preserving therapies are particularly relevant to 40% of the RB cases that are bilateral (3) . Periocular chemotherapy, selective ophthalmic artery infusion chemotherapy (SOAIC), and intravitreal (IVit) chemotherapy are relatively recent therapeutic options that have shown potential for eye-preservation (4)(5)(6) . The ultimate goal of these therapies is to deliver a locally toxic dose of chemotherapeutic agent while avoiding the systemic side effects seen in intravenous chemotherapy (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Its side effects include orbital inflammation and diffuse chorioretinal atrophy, among others (9) . The IVit chemotherapy is the most recent modality developed to deliver the chemotherapeutic agent directly into the vitreous (6,10) . Studies have shown clearing of the vitreous seeding and avoidance of enucleation in the majority of cases (6) .…”
Section: Introductionmentioning
confidence: 99%